Luigi Mongeri: A reformist and expert on "Oriental Insanity" in the Nineteenth-Century Ottoman Empire - Gündoğdu, Cihangir (My University, 2022)
This article focuses on the early career of Luigi Mongeri, who was appointed as the chief physician to the Süleymaniye Mental Asylum in 1856 to treat mental illness and improve the living conditions of mentally ill patients in the nineteenth-century Ottoman Empire. It focuses on Mongeri's early career in Italy, investigates his involvement in Ottoman imperial patronage networks and their subsequent effects on his career, and finally explores the reform program he implemented at Süleymaniye. While in the Ottoman Empire, Mongeri appeared as a reformist who claimed to improve the living conditions and treatment of patients by the use medical statistics, abolishing the use of shackles, etc. At the same time in Europe—and especially in France, which was one of the important centers of alienist medicine at the time— he presented himself as an expert on "oriental insanity,” a claim which gained him access to international medical circles and organizations.